Deconstructing Women’s Leadership: Those Who Laugh Last - Isaac, Carol (International Journal of Humanities and Social Science Research, 2018)
There is much research that illustrates the “glass ceiling” effect for women in elite leadership positions. Examining female academic chairs’ leadership in a male domain provides insight into leadership practices. The author interviewed three female clinical chairs and integrated the findings into a women's leadership model. Deconstructive thematic analysis of the subsequent text gathered systematic and in-depth information about this case at a U.S. top-tier academic medical center. A deconstructive view suggests that women leaders will be both masculine and feminine, that gender is not an issue although issues were identified by their laughter, that communal behavior may be considered a weakness but became their strength, and that threat may be “in the air" but not noticed. All three female chairs simultaneously accommodated and resisted constructs within the literature. All the barriers described in a model of women's leadership were dismantled by these successful women chairs.